Pengembangan Aplikasi Steganografi Multiformat untuk Penyisipan Data pada Media Citra, Audio, dan Dokumen Digital - Tri Mayluddin Villanda; Kelvin Alfarezy; Riski Agustio; M. Alisud Nasution (JIKUM: Jurnal Ilmu Komputer, 2026)
Information security has become a critical issue in modern digital communication, especially with the massive exchange of multimedia data across open networks. Cryptography is widely used to protect message content; however, encrypted data often attracts attention and may raise suspicion. Steganography provides an alternative approach by concealing secret data within digital media in an imperceptible manner. This study aims to develop a multiformat steganography application capable of embedding and extracting confidential data in images, audio files, and digital documents. The proposed system supports image-based least significant bit (LSB) techniques, audio LSB embedding, and document-based methods using metadata and zero-width characters. The application is implemented using Python and designed with a modular architecture to ensure extensibility and usability. Experimental results show that the application successfully embeds and extracts hidden messages across all supported media formats without causing noticeable degradation in media quality. The findings demonstrate that multiformat steganography can enhance information security by providing flexible and covert data-hiding capabilities suitable for various digital communication scenarios.